Practice of Coalition Government and its Effect on Current Economic Policy of Nepal - Dhakal, Chandra Prasad (International Research Journal of MMC, 2022)
In the context of Nepal, economic policy is guided by constitution and law. However, to some extent economic policy is guided by the manifesto of political parties and interest of key political leader. Theoretically, Nepalese economic policy is broadly guided by either socialist or capitalist ideology. Since the establishment of republic in Nepal, economic policy is guided by agenda of communist party. In this context, the study analyzes how the policy of coalition government impact overall economic plan of Nepal. The study followed the qualitative research design that analyzed the issue raised in research questions. Secondary sources of data were used for this study and conclusion of this study has been made on the basis of secondary source of the data. On the basis of data analysis, it is found that coalition government directly influenced on the economic policy of Nepal because political parties try to incorporate their minimum policy in governmental policy.